A new POM–MOF hybrid microporous material with ultrahigh thermal stability and selective adsorption of organic dyes. Issue 112 (23rd November 2016) - Huo, Miao; Yang, Wenbin; Zhang, Hailong; Zhang, Lei; Liao, Jianzhen; Lin, Lang; Lu, Canzhong
Abstract : A new POM–MOF hybrid material was synthesized under solvothermal conditions. It features a 3D host–guest microporous structure with ultrahigh thermal stability, and selectively capture MB + from binary mixtures of MB + /MO −, MB + /R6G + or MB + /RhB + . Abstract : Using Keggin heteropolyoxometalate H3 PW12 O40 as the template, a new host–guest POM–MOF hybrid material formulated as (CH3 NH2 CH3 )[Cu2 (TPB)2 (PW12 O40 )]·4DMF·6H2 O (1 ) has been successfully synthesized under solvothermal conditions. Complex1 is characteristic of a 3D host framework constructed from Cu + ions and TPB ligands and containing different types of one-dimensional channels. The larger channels along the c axis are occupied by Keggin polyoxoanions as guests, while the narrower ones along the [110] direction are available to accommodate solvent molecules and counter dimethylamine cations. Complex1 shows ultrahigh thermal stability and permanent porosity. In addition, dye adsorption and photocatalytic properties of1 have been investigated. The results indicated that complex1 is not only a good heterogeneous photocatalyst for the degradation of MO −, but also selectively captures MB + from binary mixtures of MB + /MO −, MB + /R6G + or MB + /RhB + .